Violência e trabalho: possibilidades e implicações na subjetividade do trabalhador docente - Souza, Sherry Max de (2021)
The capitalist mode of production was founded and developed based on violent processes. In this sense, it is believed that the society of capital structured itself and improves its bases of exploitation on the working class from a violent dynamic, which has been presenting more subtle, veiled and effective characteristics. From this, we begin to point out some elements that structure the historical basis of all the violence that permeates society today and, consequently, our object of study, which is the violence that affects and structures the teaching work. Within this logic, this study is outlined from a qualitative and exploratory research project, categorically conceptualized as documentary, as it worked with data capture instruments and document analysis on the theme of violence, which aimed to discuss the relationship between violence, teaching work and subjectivity. Its main objective is to verify the implications of this relationship in the constitution of subjectivity of militant teaching workers, as well as to present a conception of subjectivity and violence based on the principles of historical-dialectical materialism, considering the teaching work as an element permeated with contradictions. In this issue, violence is represented by situations of persecution, harassment, embarrassment, threat or intimidation, suffered by teachers who take a pedagogical position, considering that the teaching work has an ethical-political character. From the analysis of the interviews, it was evident that violence is subjectivated in the form of fear, illnesses, humiliation, mental disturbances, suffering, etc. Therefore, it was shown that workers react to violence in different ways, which can be in the form of suffering or different ways of preparing for new confrontations and resisting violent attacks.